2022
DOI: 10.3389/fendo.2022.1014743
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with daily growth hormone among children and adolescents with growth hormone deficiency in the UK

Abstract: BackgroundChildren with growth hormone deficiency (GHD) are treated with daily somatropin injections; however, poor treatment persistence and adherence have been recognized previously and have been shown to negatively impact growth outcomes. A recent real-world study of a US pediatric GHD population found that a substantial proportion of children discontinued somatropin therapy, but similar data for a real-world UK population are lacking.ObjectivesTo describe the discontinuation of, and persistence with, daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 4 Additionally, two retrospective studies investigating treatment adherence and persistence of children to daily GH were conducted in the USA and UK. 5 , 6 Both studies found that a high proportion of children discontinued treatment despite exhibiting early persistence. 5 , 6 For adults with GHD (AGHD), adherence to daily GH among 107 participants was investigated using a cross-sectional analysis, 7 and the results showed that older age was significantly associated with better adherence to daily GH (p = 0.021).…”
Section: Introduction To Somapacitan and Long-acting Growth Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Additionally, two retrospective studies investigating treatment adherence and persistence of children to daily GH were conducted in the USA and UK. 5 , 6 Both studies found that a high proportion of children discontinued treatment despite exhibiting early persistence. 5 , 6 For adults with GHD (AGHD), adherence to daily GH among 107 participants was investigated using a cross-sectional analysis, 7 and the results showed that older age was significantly associated with better adherence to daily GH (p = 0.021).…”
Section: Introduction To Somapacitan and Long-acting Growth Hormonesmentioning
confidence: 99%
“…5 , 6 Both studies found that a high proportion of children discontinued treatment despite exhibiting early persistence. 5 , 6 For adults with GHD (AGHD), adherence to daily GH among 107 participants was investigated using a cross-sectional analysis, 7 and the results showed that older age was significantly associated with better adherence to daily GH (p = 0.021). 7 Given trends seen in other chronic conditions requiring long-term treatment, it is likely that the high injection frequency plays a role in the increasingly low adherence to daily GH.…”
Section: Introduction To Somapacitan and Long-acting Growth Hormonesmentioning
confidence: 99%